THE COMPARATIVE MORPHOLOGICAL ALALYSIS OF THE SUBGENUS MELANOCROMMYUM (AMARYLLIDACEAE, ALLIOIDEAE) IN UZBEKISTAN (Scientific journal of the Fergana State University, 2026)
The genus Allium (Amaryllidaceae) is a taxonomically complex and morphologically diverse group, with the subgenus Melanocrommyum representing a significant portion of Central Asia's Allium species. This study presents a detailed morphological analysis of Melanocrommyum species in Uzbekistan, combining field-collected samples and herbarium specimens. We focused on six key morphological traits filament length, perianth color, flower density, sheathy prophyll length, leaf shape, and inflorescence density mapped onto a phylogeny constructed from both molecular (ITS and trnL-trnF sequences) and morphological data. Our analysis reveals patterns of synapomorphy, homoplasy, and evolutionary plasticity across species. The results highlight the utility of combining morphological character mapping with molecular data to refine taxonomic classifications and contribute to a more comprehensive understanding of Melanocrommyum systematics.